Religions of the world - Hopfe, Lewis M. 1935-1992.; Woodward, Mark R. 1952-. (Upper Saddle River, N.J. Prentice Hall, 2001)
Offers accurate, comparative descriptions of a broad range of religions and explores living religions in terms of historical and cultural factors that produced them, the lives of their founders, their basic teachings, and their historical development and current status in the world.
Basic religions -- 1. Characteristics of basic religions -- 2. Native American religions -- 3. African religions -- Religions originating in India -- 4. Hinduism -- 5. Jainism -- 6. Buddhism -- 7. Sikhism -- Religions originating in China and Japan -- 8. Chinese religions -- 9. Shinto -- Religions originating in the Middle East -- 10. Zoroastrianism -- 11. Judaism -- 12. Christianity -- 13. Islam -- 14. Baha'i -- Glossary -- Credits -- Index.
Keywords: Religions -- Textbooks